A Randomized Control Trial of Working Memory Training With and Without Strategy Instruction: Effects on Young Children's Working Memory and Comprehension. (January 2017) - Peng, Peng; Fuchs, Douglas
Researchers are increasingly interested in working memory (WM) training. However, it is unclear whether it strengthens comprehension in young children who are at risk for learning difficulties. We conducted a modest study of whether the training of verbal WM would improve verbal WM and passage listening comprehension and whether training effects differed between two approaches: training with and without strategy instruction. A total of 58 first-grade children were randomly assigned to three groups: WM training with a rehearsal strategy, WM training without strategy instruction, and controls. Each member of the two training groups received a one-to-one, 35-min session of verbal WM training on each of 10 consecutive school days, totaling 5.8 hr. Both training groups improved on trained verbal WM tasks, with the rehearsal group making greater gains. Without correction for multiple group comparisons, the rehearsal group made reliable improvements over controls on an untrained verbal WM task and on passage listening comprehension and listening retell measures. The no-strategy-instruction group outperformed controls on passage listening comprehension. When corrected for multiple contrasts, these group differences disappeared but were associated with moderate to large effect sizes. Findings suggest—however tentatively—that brief but intensive verbal WM training may strengthen the verbal WM and comprehension performance of young children at risk. Necessary caveats and possible implications for theory and future research are discussed.